Demonstration of ferroelectricity in ScGaN thin film using sputtering method - Uehara, Masato; Mizutani, Ryoichi; Yasuoka, Shinnosuke; Shiraishi, Takahisa; Shimizu, Takao; Yamada, Hiroshi; Akiyama, Morito; Funakubo, Hiroshi (Applied physics letters, 2021)
It is recently found that wurtzite aluminum nitride exhibits ferroelectricity by alloying with scandium. Because its remanent polarization (Pr) is large, ScxAl1−xN has attracted much attention. Gallium nitride with similar structure and properties is also expected to show ferroelectricity. Herein, ScxGa1−xN was prepared on a silicon substrate at 673 K using the sputtering method, and its ferroelectricity was investigated. Sc0.41Ga0.59N exhibited ferroelectricity before dielectric breakdown. Pr of this film, as evaluated via positive-up-negative-down (PUND) measurement, was around 120 μC/cm2, which can reduce the influence of the leakage current. This was comparable to the value of ScxAl1−xN with the same internal parameter u, which is approximately estimated from the lattice constants. Moreover, in the PUND measurement, the measurement temperature dependence of Ec was observed, which was 4.3 MV/cm at 300 K and reduced to 3.2 MV/cm at 473 K.